Logistics Customer Service in The E-Commerce Market in Poland - Joanna DYCZKOWSKA; Marcin OLKIEWICZ; Dagmara PASZKOWSKA (Communications of International Proceedings, 2022)
Electronic commerce (e-commerce) has changed the process of buying, selling and exchanging products, services or information via computer networks. The aim of the study was to analyse the e-commerce market together with the customer service process. The research methods used a literature analysis and an indirect diagnostic survey.  The most important criteria was the price - it got 85%, then punctuality of delivery, which got approximately 80%. Payment terms received the lowest rating (57%). The rest of the criteria ranged from 65% to 79.6%.
Keywords: e-commerce; logistics; customer; service